Relationship of diametrical and axial methods of testing for point load index of rock / Nor Fazlin Raduaani - Raduaani, Nor Fazlin (1997)
The study is concerned with the use of the point load testing measurements to predict the point load strength. The estimated point load index, Is(50) are found from the formula of size correction factor time the point load strength index, Is. While, the point load strength index, Is, been determined from the load applied at the diameter of the specimen. The comparison of the two output, i.e Axial point load index, Isa and Diametral point load index,Z«/. The point load test are carried out on the samples of malaysian rocks i.e. Sandstone and Granite. The experimental data of point load index is related with the theories given by the researchers such as brooch and Franklin, bieniawski and etc.